Separating the stratospheric and tropospheric pathways of El Niño–Southern Oscillation teleconnections ... - Butler, Amy H.; Polvani, Lorenzo M.; Deser, Claira (Columbia University, 2014)
The El Niño–Southern Oscillation (ENSO) is a major driver of Northern Hemisphere wintertime variability and, generally, the key ingredient used in seasonal forecasts of wintertime surface climate. Modeling studies have recently suggested that ENSO teleconnections might involve both a tropospheric pathway and a stratospheric one. Here, using reanalysis data, we carefully distinguish between the two. We first note that the temperature and circulation anomalies associated with the tropospheric pathway are nearly equal and opposite during the warm (El Niño) and cold (La Niña) phases of ENSO, whereas those associated with the stratospheric pathway are of the same sign, irrespective of the ENSO phase. We then exploit this fact to isolate the two pathways. Our decomposition reveals that ENSOs climate impacts over North America are largely associated with the tropospheric pathway, whereas ENSOs climate impacts over the North Atlantic and Eurasia are greatly affected by the stratospheric pathway. The stratospheric ...